URGENSI PENDIDIKAN KARAKTER PESERTA DIDIK DI SEKOLAH - Ramadhana, Ari; Aceng Amrulloh; Aan Hasanah; Bambang Samsul Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Shaping the moral character of students is crucial, given the numerous negative perceptions in society regarding the failures of the education system in Indonesia, particularly at the secondary and higher education levels. The importance of character education from an early age in Indonesia is highlighted due to the decline in student morality in the era of globalization. Morality is considered an indicator of the quality of life in society. Religious individuals believe that religious teachings encourage followers to behave well and avoid wrongdoing. Character education must be taught systematically and holistically using the methods of knowing the good, loving the good, and acting the good. Character education is seen as a solution to overcoming contemporary challenges in the school environment. Keywords: Urgency of Character Education, Students, Schools;